Fairness mechanism in multiplayer online battle arena games - Mingyang Wu; Shuo Xiong; Iida, Hiroyuki (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
This paper explores key factors to maintain fairness in e-sports like Multiplayer Online Battle Arena (MOBA) games: Dota 2, League of Legends, and Heroes of the Storm. It analyzes the degree of fairness based on the winning ratio. Moreover, it considers the evolution of MOBA games with focus on three major factors: the ban and pick system, balancing characters and maps, and compares with other games such as board games and sports games. It is found that fairness is important but not so essential in the domain of e-sports from entertainment's point of view, even though fairness is significantly important in the domain of sports and board games.